Identification and systematics of safety hazards in surface rock mining - Paweł Strzałkowski; Justyna Woźniak; Justyna Górniak-Zimroz; Barbara Delijewska; Paweł Bęś; Dagmara Solatycka; Mateusz Janiszewski (Scientific Reports)
Abstract The necessity to ensure safety in the work environment is a priority for the functioning of mines as enterprises with a high level of exposure to hazards. The basis for this is the identification of hazards to which mine workers are exposed. This article aims to identify and systematize safety hazards present in quarries. Based on a review of the literature, hazards were identified and classified into six groups: natural, environmental, technical and technological, human, organizational, and others. Additionally, a correlation was established between the identified hazards and the stages of the mine’s life cycle, as well as the methods of deposit extraction in quarries. The results presented in the article systematize existing knowledge on industry-specific hazards. The results can serve as a source of information when developing occupational risk documentation and its analysis, and form the basis for research on the causes and consequences of accidents in mining. Identifying hazards can also help effectively monitor them effectively and implement preventive measures to protect workers and reduce accident risks in quarries.